2007
DOI: 10.1097/wnf.0b013e31803354f6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Olanzapine With Opioid-Agonists in the Treatment of Heroin-Addicted Patients Affected by Comorbid Schizophrenia Spectrum Disorders

Abstract: The objective of this study was to evaluate the efficacy of olanzapine (OLA) in heroin-dependent patients affected by comorbid schizophrenia spectrum disorders (SSD). Sixty-one patients who met the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria for heroin dependence and the criteria for SSD (schizophrenia and schizotypal and schizoaffective-bipolar disorders) were treated in a 12-week prospective observational trial of substitution treatment in combination with OLA or typical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…One open study in heroin-dependent patients with comorbid schizophrenia found those on olanzapine remained longer in treatment and revealed more negative urine analyses for illicit drugs compared with those on haloperidol treatment (Gerra et al, 2007) …”
Section: Relapse Prevention Medication In Schizophrenia: Opioidsmentioning
confidence: 99%
“…One open study in heroin-dependent patients with comorbid schizophrenia found those on olanzapine remained longer in treatment and revealed more negative urine analyses for illicit drugs compared with those on haloperidol treatment (Gerra et al, 2007) …”
Section: Relapse Prevention Medication In Schizophrenia: Opioidsmentioning
confidence: 99%
“…There are relatively few reports about schizophrenic patients and methadone treatment with even less focusing on retention. From what research is available, it has been reported that the atypical antipsychotic, Olanzapine, may increase retention in schizophrenia patients with opiate addiction [13,34]. Methadone has very occasionally been used to treat psychotic symptoms [35], which may be part of an explanation of this putative effect.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…However, it is important to note that any increase in methadone dose needs to be balanced with side effects-respiratory depression, constipation, hypotension, drowsiness and increased dependencethat may occur at higher concentrations [39]. The second treatment implication is that prescription of antipsychotic medication to patients with psychotic disorders may improve retention in that population [34]. Finally, a number of areas that would benefit from further research can be identified.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In another open study, heroin-dependent patients with comorbid schizophrenia had more negative urine analyses for illicit drugs with olanzapine than with haloperidol and remained in treatment for longer [46] . Case series have demonstrated superior improvement of psychopathology and craving [47] with olanzapine than with haloperidol, and a retrospective analysis of a prospective first-episode study reported a lower drop-out rate [48] .…”
Section: Second-generation Antipsychoticsmentioning
confidence: 99%